BOOK REVIEW OF THE LAST SONG WRITTEN BY NICHOLAS SPARKS - Bayu, Ari (LANTERN (Journal on English Language, Culture and Literature), 2015)
Literature such as novel is one of human works, presents some character‟s struggle inseveral circumstances. In which influences and entertain the reader. The purpose of TheLast Song written by Nicholas Sparks review are explains the theme and the struggle ofthe main character as the strength of the novel, and the weakness. Based on the review,the novel has theme about the affection for God, Family members, friends, and nature.Affection is something beautiful. Someone is getting affection to get happiness. Thisnovel has the struggle of a main character that is a struggle from father to reconcile hisrelationship with his daughter. On the other hand, the weakness from this novel is aboutthe song finished by main character, the readers may be disappointed with the endingfrom this novel. There is no detail or description about the lyrics and intonation about thatsong. The Last Song is a suitable novel read by people who wants to struggle and to haveaffection in daily life. It reminds the readers of the truly important things in life and givesthe readers a look at love, joy, peace, patience and kindness.